Investigation on properties of mortar with the use of simply shredded post-consumer plastic waste aggregate and molasses - Ghanshyam Dumre; Kushal Rana Bhat; Tek Raj Gyawali (Heliyon)
The world faces significant challenges in managing plastic waste, which does not decompose and releases toxic gases when burned, posing severe health hazards. Concurrently, Nepal's heavy burnt-clay brick walls in reinforced concrete building structures urgently need replacement with lightweight walls. To tackle these dual challenges, this paper uniquely explores the innovative reuse of post-consumer plastic waste aggregate (PWA) as a sustainable alternative to sand, aiming to produce lightweight mortar for enhanced building applications. The control mortar used a water: cement: sand ratio of 1:2:4 (by weight). Shredded PWA was incorporated at varying contents of 0.00 %, 2.50 %, 5.00 %, 7.50 %, and 10.00 % by weight of sand. The study also examined the effect of adding 0.05 % molasses by weight of cement on the mortar's properties. The physical, mechanical, and water absorption properties of each mortar mix were evaluated using standard tests. The table flow value and water absorption of the mortar with 10.00 % PWA content increased by 20.83 % and 148.72 %, respectively, compared to the control mortar. However, the 28-day compressive, flexural, and splitting tensile strengths decreased by 92.29 %, 41.70 %, and 83.26 %, respectively. It was feasible to use 7.50 % and 10.00 % PWA to produce lightweight panels for walls, with and without molasses, respectively. The use of PWA in concrete addresses critical plastic waste management challenges while enabling the production of sustainable structural and non-structural concrete. PWA mortar can replace heavy brick walls, reducing building weight and enhancing seismic resistance. Additionally, substituting brick walls lowers reliance on brick kilns, leading to reduced CO₂ emissions and land degradation, while also cutting concrete production costs.